Investor’s Expected Profit from Viatical Settlements - Dębicka, Joanna; Heilpern, Stanisław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
For an insured person who needs money because of suffering from a terminal illness that requires costly diagnosis and treatment, the easiest way of receiving money from life insurance is to withdraw from the contract of insurance. Then the insurer is obliged to pay the surrender value of policy. It appears that there is another possibility for the insured to receive prior financial gratification from life insurance. The insured can sell his policy on the secondary market of life insurance (the viatical market). In such a situation he obtains an amount that is greater than the surrender value (and less than the death benefit). Then the viatical company takes a fee for the insurance premiums, and in case of death of the insured gets the death benefits. Such agreements to resell the rights to death benefits are offered to people who have become terminally ill (viatical settlement). The aim of the paper is to study the influence of the moment of falling ill (compared to the age and sex of the insured and duration of insurance) on the expected profit of the viatical company. For this purpose, we apply the methodology used by insurance companies in the valuation of the contract
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 105-116
Keywords: viatical market; life insurance; multistate model